Peran Orang Tua Dalam Pembelajaran Daring PAI Masa Pandemi Covid-19 Peserta Didik Kelas X IPS SMAN 107 Jakarta Tahun Pelajaran 2020-2021 - Murtafi’ah, Murtafi’ah; Adawiyah, Rabiatul (MADINAH, 2020)
The role of parents in online learning during the COVID-19 pandemic is very different from the role of parents in the normal era. One of the differences is in the process of mentoring learning. Many parents feel burdened by online learning, so problems arise in it. Including at SMAN 107 Jakarta, many problems were found in online learning. The aims of this study are: (1) To explain the role of parents in online learning at SMA Negeri 107 Jakarta in the 2020/2021. (2) To explain the differences and similarities in how to assist parents in the online learning process at SMA Negeri 107 Jakarta. (3) To analyze the difficulties faced by parents in online learning at SMA Negeri 107 Jakarta. The method used in this research is qualitative descriptif. Data collection techniques in this study used observation, interviews, tagged questionnaires and documentation. For data analysis techniques, there are 3 stages used, namely data reduction, presentation, and verification. Then, to test the validity of the data, this thesis uses triangulation. The results of this study found that in the implementation of online learning, students of class X IPS SMA Negeri 107 Jakarta used the Zoom meeting application and WhatsApp group. The reason, because it is more popular and simpler. In addition, they also use Google Classroom, especially in practice questions or exams. The roles of parents in this learning activity are listed as follows: (1) assisting children in learning and doing assignments, (2) supervising children in using cellphones, (3) helping explain material if there is something they don't understand, (4) providing facilities learning such as cellphones or internet quotas, (5) providing motivation or support, (6) providing solutions to any obstacles and problems in online learning.